2015
DOI: 10.1016/j.cmet.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Brown and Beige Fat: Physiological Roles beyond Heat Generation

Abstract: Since brown adipose tissue (BAT) dissipates energy through UCP1, BAT has garnered attention as a therapeutic intervention for obesity and metabolic diseases including type2 diabetes. As we better understand the physiological roles of classical brown and beige adipocytes, it is becoming clear that BAT is not simply a heat-generating organ. Increased beige fat mass in response to a variety of external/internal cues is associated with significant improvements in glucose and lipid homeostasis that may not be entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
763
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 819 publications
(778 citation statements)
references
References 162 publications
(238 reference statements)
9
763
1
5
Order By: Relevance
“…conclusions regarding the similarities and differences between brown and beige adipocytes (Harms and Seale, 2013;Kajimura et al, 2015;Lee et al, 2017b;Waldén et al, 2012). The development and function of BAT has been discussed extensively elsewhere Kajimura et al, 2015), therefore, here, we focus on the developmental and functional heterogeneity of WAT depots and white adipocyte populations.…”
Section: Adipose Tissue Depotsmentioning
confidence: 99%
“…conclusions regarding the similarities and differences between brown and beige adipocytes (Harms and Seale, 2013;Kajimura et al, 2015;Lee et al, 2017b;Waldén et al, 2012). The development and function of BAT has been discussed extensively elsewhere Kajimura et al, 2015), therefore, here, we focus on the developmental and functional heterogeneity of WAT depots and white adipocyte populations.…”
Section: Adipose Tissue Depotsmentioning
confidence: 99%
“…Adipocytes comprise three subtypes: white adipocytes, brown adipocytes and inducible brown-like adipocytes found interspersed in WAT depots (Kajimura et al, 2015;Wang and Seale, 2016). The latter are most commonly referred to as brite (brown-in-white adipocytes) or beige adipocytes (Klingenspor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Brown adipose tissue aids with acclimatization to cold through its unique ability to generate heat by uncoupling cellular respiration from mitochondrial adenosine triphosphate (ATP) synthesis. [4][5][6] Based on findings from studies involving animals and humans, the effects of brown adipose tissue activation extend beyond thermogenesis, by influencing whole-body metabolism and possibly overall body weight. [7][8][9][10][11][12][13][14][15][16][17][18] Small intervention trials involving humans have suggested that even mild exposure to ambient cold -such as lowering a thermostat from 24°C to 19°C -can increase activity of brown adipose tissue by 30%-40%, resulting in substantial improvements in insulin sensitivity.…”
mentioning
confidence: 99%